Tensile Capacity of Concrete Pile Foundation at the Surajaya Stadium Tribune in Lamongan - Muhammad, Setia Budhi; Hanie, Teki Tjendani; Erni, Puspanantasari Putri (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The Surajaya Stadium Tribune foundation consists of 772 concrete piles divided into three zones with varying compression and tensile capacities, necessitating verification for safety and efficiency. This study evaluates the effectiveness of static versus dynamic testing methods for determining the tensile capacity of these piles. The analysis employs Driving Record, Pile Driving Analyzer (PDA), and CAPWAP methods, focusing on three evaluation approaches: Minimum Bearing Capacity Factor (FDDmin), Average Bearing Capacity Factor (FDDavg), and CAPWAP Friction Bearing Capacity. Results indicate that all methods yield a safety factor (SF) exceeding 2, confirming compliance with design criteria, with average SF of 2.73 (FDDmin), 3.02 (FDDavg), and 2.51 (CAPWAP). Additionally, substituting static tensile tests with modified dynamic tests can save up to 36 days and Rp 1,299,077,600 in costs. While dynamic methods offer efficiency, they may compromise data accuracy, highlighting the need for experienced vendors and calibrated equipment to enhance testing precision.